Metabolomic Profiling Reveals Changes in Amino Acid and Energy Metabolism Pathways in Liver, Intestine and Brain of Zebrafish Exposed to Different Thermal Conditions - Andrea Aguilar; Humberto Mattos; Beatriz Carnicero; Nataly Sanhueza; David Muñoz; Mariana Teles; Mariana Teles; Lluis Tort; Sebastian Boltaña (Frontiers in Marine Science, 2022)
Global warming is predicted to increase prolonged thermal challenges for aquatic ectotherms, i.e. it causes metabolic performance declines, impacts food intake, and finally causes impaired growth. In this research work, we investigated whether a tropical fish, Danio rerio (zebrafish), could tolerate prolonged thermal challenges and whether the temperature increase has a significant impact on growth and metabolism. To answer our questions, we evaluate the metabolomic performance, a question that has received little attention so far, using differential chemical isotope labeling (CIL) liquid chromatography-mass spectrometry (LC-MS). Three groups of fish were exposed to various temperatures of 27.6 ± 2°C, 30.7 ± 2°C or 32.2 ± 2°C during 270 days post fecundation (dpf) to evaluate the impact of the temperature increase on the growth and metabolomic performance. The results obtained demonstrated different metabolomic changes in response to acclimation to the different temperatures. After 270 days, the fish maintained at the highest tested temperature (32°C) showed reduced growth, reduced condition factor, and elevated levels of metabolites associated with amino acid catabolism and lipid metabolism pathways in the liver and intestine compared with fish kept at lower temperatures (27.6 ± 2°C). These findings demonstrate an explicit redistribution of energy stores and protein catabolism in fish at the highest temperature, thus showing a preference for maintaining length growth during limited energy availability. Moreover, here we also screened out both the marker metabolites and the altered metabolic pathways to provide essential insights to ascertain the effects of the water temperature increase on the growth and development of tropical fish.